1985
DOI: 10.1128/aac.27.5.832
|View full text |Cite
|
Sign up to set email alerts
|

Activity of UK-49,858, a bis-triazole derivative, against experimental infections with Candida albicans and Trichophyton mentagrophytes

Abstract: The therapeutic potential of UK-49,858, a difluorophenyl bis-triazole derivative, has been assessed by evaluating its activity against systemic infections with Candida albicans in normal mice and rats and in mice with impaired defence mechanisms, against vaginal infections with C. albicans in mice, and against dermal infections with Trichophyton mentagrophytes in guinea pigs. Orally administered ketoconazole was used as a comparative agent throughout, and parenterally administered amphotericin B was included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
51
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(53 citation statements)
references
References 12 publications
1
51
0
1
Order By: Relevance
“…One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37). Recently, the antifungal efficacy of Flu was demonstrated in persistently granulocytopenic rabbits when it was used for prevention or early treatment (39,40).…”
mentioning
confidence: 99%
“…One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37). Recently, the antifungal efficacy of Flu was demonstrated in persistently granulocytopenic rabbits when it was used for prevention or early treatment (39,40).…”
mentioning
confidence: 99%
“…injection in treating normal AKR and C57BL/6 mice infected with Histoplasma capsulatum (7). Others have reported that fluconazole was more effective than the imidazole ketoconazole in treating normal mice (12,14) and rats (12,13) (14) reported that fluconazole was more than 20 times as effective as ketoconazole in C. albicans-infected mice that were immunocompromised by daily administration of dexamethasone. Fluconazole is an attractive antifungal agent in that (i) it is less toxic than amphotericin B, (ii) it is renally excreted, (iii) it readily penetrates cerebral spinal fluid, and (iv) it has a high serum half-life that can be maintained by daily oral administration (5).…”
mentioning
confidence: 99%
“…UK 49,858 has been shown to have a broader spectrum of activity then ketoconazole (6). For example, the doses of UK 49,858 that prevented death of 50% of mice given a lethal dose of Aspergillus flavus were 4-to 20-fold lower than ketoconazole doses in this model of infection (Troke et al IXth Int.…”
mentioning
confidence: 99%
“…Like ketoconazole, it is active when given orally and well tolerated by healthy human volunteers; doses of 1.4 mg/kg for 7 consecutive days and up to 0.7 mg/kg for 28 consecutive days have not shown any toxicity (Investigator's Reference Manual, Pfizer Inc., Groton, Conn., 1984). Orally administered UK 49,858 also appears to possess activity superior to that of ketoconazole in mice with lethal Candida albicans (6) and Aspergillus flavus (P. F. Troke, R. J. Andrews, M. S. Marriott, and K. Richardson (4). Saccharomyces cerevisiae (HLR), originally obtained from Hoffman-LaRoche, Inc., Nutley, N.J., was used as a drug control organism for our susceptibility studies.…”
mentioning
confidence: 99%